Different profiles of fatty acids in Ca soaps on dissociation and modification by biohydrogenation in vitro - Cappellozza,Bruno Ieda (2020)
ABSTRACT This study evaluated the effects of rumen pH on in vitro Ca dissociation of different sources of Ca soaps of fatty acids (CSFA). Treatments were distributed in a 6×4 factorial design and consisted of six CSFA sources and four rumen fluid pH. The CSFA sources were: two sources of palm oil (PO1 and PO2), soybean oil (SO), palm + soybean oil (PSO), palm + cottonseed oil (PCO), and palm + cottonseed + soybean oil (PCSO). All CSFA samples were added to a pool of rumen fluid and adjusted to four different pH (5.5, 6.0, 6.5, and 7.0), and then, incubated at 37 °C for 1 h. This procedure was replicated over three consecutive days. Effect of CSFA source × rumen pH was detected for in vitro relative Ca dissociation and change (Δ) in concentrations of oleic, linoleic, and linolenic acids. Calcium dissociation did not differ among CSFA sources in pH 7.0 or 6.5, but was greater for SO vs. PO2, PSO, PCO, and PCSO in pH 6.0. Relative Ca dissociation in pH 5.5 was lower for PO1 and PSO vs. SO, but greater for PO1 and PSO vs. PCO and PCSO. The Δ of oleic acid was greater for PO2 vs. PCO in pH 6.5 and PO1 and PCSO vs. PO2 and SO in pH 7.0. The Δ of linoleic acid was greatest for SO across all pH evaluated and did not differ between PO1 and PO2, but both had a reduced Δ of linoleic acid than other CSFA sources in pH 5.5 and 7.0. The Δ of linolenic acid concentrations did not differ between PO1 and PO2, but both had less Δ of linolenic acid concentrations than other CSFA sources across all pH. Besides, SO had greater Δ of linolenic acid compared with PSO, PCO, and PCSO in pH 5.5, 6.0, and 6.5. Combining palm + cottonseed oil and palm + cottonseed + soybean oil reduces Ca dissociation and maintains the original fatty acid profile of the CSFA source.